Protocolo para pruebas de seguridad eléctrica en equipos electro médicos: caso de estudio - Calderón Romero, Fernely Sebastian (Universidad Antonio Nariño, 2021)
In Colombia, the National Program of Technosurveillance, belonging to INVIMA, is the set of activities that allows the identification, evaluation, management and dissemination of information on incidents and adverse events due to the use of medical devices. However, with regard to the electrical safety of these devices, ICONTEC, according to Decree 2269 of 1993, adopted as a Colombian technical standard, what was proposed by the International Electrotechnical Commission (NTC/IEC 60601-1) to ensure the proper functioning of electromedical equipment. In this internship work, we intend to develop, with the company grandtek S.A.S, the study of the standard and create a verification and evaluation protocol, to guarantee the electrical safety tests of electromedical equipment. And thus be able to provide this service, to perform and certify the electrical safety tests on electromedical equipment that is part of a preventive maintenance program required by Decree 4725.